Mixed-dimensional membranes: chemistry and structure-property relationships - Liu, Yanan; Coppens, Marc-Olivier; Jiang, Zhongyi (Chemical Society reviews, 2021)
Tremendous progress in two-dimensional (2D) nanomaterial chemistry affords abundant opportunities for the sustainable development of membranes and membrane processes. In this review, we propose the concept of mixed dimensional membranes (MDMs), which are fabricated through the integration of 2D materials with nanomaterials of different dimensionality and chemistry. Complementing mixed matrix membranes or hybrid membranes, MDMs stimulate different conceptual thinking about designing advanced membranes from the angle of the dimensions of the building blocks as well as the final structures, including the nanochannels and the bulk structures. In this review, we survey MDMs (denoted n D/2D, where n is 0, 1 or 3) in terms of the dimensions of membrane-forming nanomaterials, as well as their fabrication methods. Subsequently, we highlight three kinds of nanochannels, which are 1D nanochannels within 1D/2D membranes, 2D nanochannels within 0D/2D membranes, and 3D nanochannels within 3D/2D membranes. Strategies to tune the physical and chemical microenvironments of the nanochannels as well as the bulk structures based on the size, type, structure and chemical character of nanomaterials are discussed. Some representative applications of MDMs are illustrated for gas molecular separations, liquid molecular separations, ionic separations and oil/water separation. Finally, current challenges and a future perspective on MDMs are presented. This review highlights the design and construction of mixed-dimensional membranes (MDMs) and their applications in molecular separations, ionic separations and oil/water separations.